Biomarkers used to monitor heavy metal exposure in metallurgy - Ramírez, Augusto V. (2006)
Worker’s health is the most important fact in heavy metal exposition surveillance. In extractive metallurgy there is exposition to many elements and chemical compounds. Current laboratory technological advances allow us to develop biologic media’s measurements for use in occupational health assessment. Monitoring is measuring, assessing and interpreting biological media and environment parameters, to prevent and avoid health risks. It implies establishing control measures in labor environment defining exposition levels not causing adverse effects on workers. An exposition’s biological indicator doses blood metal or byproducts biotransformation into biological media in order to quantify body chemistry. In kidney toxicity, we use function and citotoxicity indicators, low molecular weight proteins and urinary enzymes. In neurological toxicity, substitute indicators are being developed. And in genotoxicity, DNA adducts. This paper revises indicators for main heavy metals in extractive metallurgy.